THE EFFECT OF JOB SELF-EFFICACY ON JOB ENGAGEMENT WITH AN EMPHASIS ON THE ROLE OF WORK-LIFE BALANCE. CASE STUDY: NATIONAL LAND AND HOUSING ORGANIZATION OF TEHRAN - Mahsa NAGHSHINEH (Management & Marketing, 2022)
The purpose of this study was to provide a predictive model of job engagement based on self-efficacy effect and moderating effect of work-life balance of employees of National Land and Housing Organization of Tehran. To this end, 160 people (75 men and 85 women) were selected by stratified random sampling, and a questionnaire consisting of job engagement components (Schaufeli, 2003), job self-efficacy (Riggs and Knight, 1994), and Work-Life balance (Wong et al., 2009). SPSS software was used to analyze the questionnaires. The Kolmogorov-Smirnov test was used to measure the normality of the data and the results showed that the data collected from the normal population. To investigate the relationship between variables, we used Pearson correlation coefficient and the results showed that all variables have a positive and significant relationship. To test the research hypotheses, we used a structural equation model for which the Lisrel 8.8 software was used. The findings showed that the dimensions of job self-efficacy and work-life balance positively and directly Effected the job engagement.